(untitled) - Gibbon, Edward (Chicago, 1990)
Edward Gibbon’s classic timeless work of ancient Roman history in 6 volumes collected into 2 boxed sets, in beautiful, enduring hardcover editions with elegant cloth sewn bindings, gold stamped covers, and silk ribbon markers.
Keywords: Rô-ma,Rome; Lịch sử,History; Đế chế, 30 B.C.-476 A.D.,Empire, 30 B.C.-476 A.D.